Environmental Impact Assessment of Brick Production in Indonesia - Tatbita Suhariyanto; Hayati Mukti Asih; Fadli Surya Ramadhan; Ahmad Rijal Nasution (Engineering Science Letter, 2022)
Brick is one of the building materials commonly used in building construction materials. The production activities of the brick industry have a lot of potential that can cause problems in the environment such as water, soil and air pollution. The purpose of this study is to analyze the potential environmental impacts in the form of emissions and waste from brick production activities by applying the LCA method to the brick production process and to identify the inputs and outputs of the brick production process. To gain a deep understanding, a small enterprise of brick manufacturer was selected as a case study. The results of this study indicate that electricity and cement are the biggest causes of each category of impact. The category of potential global warming impact is the largest with a total of 6.95 kg CO2-eq. Although in all categories the percentages are more or less the same. This happens because the brick production process which almost entirely uses electrical energy in the production process and also the use of cement in large quantities has a major impact on the environmental impact.